Splenic abscess as a rare symptom of the extrapulmonary tuberculosis - case report - Horák, P; Horová, B; Koutníková, H; Marvan, J; Fulík, J; Fanta, J (Rozhledy v chirurgii, 2019)
INTRODUCTION: Extrapulmonary tuberculosis can involve any organ or tissue. It is a rare disease in the Czech Republic with an incidence rate of 0.62 cases per 100.000 persons. It affects mostly immunocompromised patients. The most common sites include lymph nodes, the urogenital system, skin, joints, bones and serous epithelium - the peritoneum, pleura, and pericardium. Splenic involvement is rare. Mycobacterium is a slow growing intracellular parasite. The diagnostic process is very difficult; microbiological diagnosis is critical. CASE REPORT: An 84 years old female patient with subcapsular splenic rupture with no trauma history as a cause of anemia. Splenic abscess was diagnosed during surgical revision and splenectomy. Tuberculosis was suspected based on subsequent histological analysis, which was confirmed after nine weeks of peritoneal fluid culture. The surgical procedure and postoperative hospitalization were not associated with any complications. The patient was referred to the respiratory clinic for further treatment. CONCLUSION: The diagnosis of extrapulmonary tuberculosis including splenic localization should always be considered. A sample from the affected tissue or effusion must be collected in the case of unclear perioperative findings and sent for complete bacteriological testing, including mycobacterial culture. If a tuberculous splenic abscess is found, the therapeutic process should involve its complete drainage in combination with long-term anti-TB medication.
Keywords: absces; abscess; senioři nad 80 let; splenectomy; Česká republika; Mycobacterium tuberculosis; tuberkulóza; ruptura sleziny; Czech Republic; Splenic Diseases; splenic tuberculosis; Aged, 80 and over; ženské pohlaví; Humans; splenektomie; nemoci sleziny; Abscess; Tuberculosis; Splenectomy; Splenic Rupture; Female; lidé